2006
DOI: 10.1590/s0102-76382006000100007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do EuroSCORE como preditor de mortalidade em cirurgia de revascularização miocárdica no Instituto do Coração de Pernambuco

Abstract: Objective: To assess the applicability of the European Risk Score System in Cardiac Operations (EuroSCORE) in patients undergoing myocardial revascularization at the Heart Institute of Pernambuco.Method: From 2003 to 2004, 759 patients underwent myocardial revascularization. For the study, seven were excluded due to the lack of information on one aspect or another involved in obtaining the EuroSCORE. In order to assess the applicability of the EuroSCORE, an adjustment was made using a logistic regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 18 publications
3
24
0
2
Order By: Relevance
“…Moraes et al [17] performed a validation study in 752 patients undergoing coronary artery bypass grafting (CABG) at a Brazilian institution in the State of Pernambuco, demonstrating that the EuroSCORE obtained good prediction of mortality (similar to that expected). However, there are doubts about the fact that this study [17] is representative of cardiac surgeries performed in public institutions in the State of Pernambuco, once it was conducted in a private institution. Recently, Carvalho et al [18] advised against the use of the EuroSCORE as a tool for assessment of operative risk in patients who were to undergo CABG in public hospitals in Rio de Janeiro, in view of the low discriminatory power observed in that study.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Moraes et al [17] performed a validation study in 752 patients undergoing coronary artery bypass grafting (CABG) at a Brazilian institution in the State of Pernambuco, demonstrating that the EuroSCORE obtained good prediction of mortality (similar to that expected). However, there are doubts about the fact that this study [17] is representative of cardiac surgeries performed in public institutions in the State of Pernambuco, once it was conducted in a private institution. Recently, Carvalho et al [18] advised against the use of the EuroSCORE as a tool for assessment of operative risk in patients who were to undergo CABG in public hospitals in Rio de Janeiro, in view of the low discriminatory power observed in that study.…”
Section: Introductionmentioning
confidence: 83%
“…An important aspect is the fact that we are studying a population undergoing operations at a public institution. Moraes et al [17] performed a study involving 752 patients undergoing CABG in private institution, showing a mortality rate of 1.7%. On the other hand, Oliveira et al [20] recently published a study involving public hospitals and showed an in-hospital mortality rate ranging from 7% to 14.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is particularly important when dealing with critically-ill patients, since the data attained by logistic regression of the independent variables are closer of the reality observed. Data from EuroScore surgical forecast were also validated for Brazilian patients [12].…”
Section: Databasementioning
confidence: 99%
“…This group of patients, due to the aging process itself, has comorbidities that increase the operative risk 5,6 . One of the most widely used risk scores today, the EuroSCORE 7,8 , applies a significant weight to age over 60 years in the final calculation of mortality risk. However, it seems reasonable to consider all the elderly patients as a homogeneous group, and age, by itself, as a determinant of greater risk 9,10 .…”
Section: Introductionmentioning
confidence: 99%